EFEKTIVITAS KEBIJAKAN PENYEDERHANAAN STRUKTUR ORGANISASI PERANGKAT DAERAH KABUPATEN PEMALANG DI KABUPATEN PEMALANG - Ulfa, Nera Lutfyani; Kurniasih, Denok; Tobirin, Tobirin (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2023)
The government strives to realize good governance. One way to do this is by issuing a bureaucratic simplification policy. This policy is implemented through simplifying the structure of Regional Apparatus Organizations (OPD). The purpose of this research The purpose of this research is to analyze the OPD simplification policy of the regional government of Pemalang Regency. This research uses a qualitative descriptive research method with a case study approach with dimensions based on Edward III's theory, namely communication, resources, disposition and bureaucratic structure. The results of this research using a study of the effectiveness of the organizational structure simplification policy in the Regional Government of Pemalang Regency have gone according to expectations, despite experiencing several obstacles. To support the effectiveness of simplifying the organizational structure within the regional government of Pemalang Regency, suggestions can be given regarding the availability of human resources needed to support the policy so that it runs more effectively.